Substantiation of the effectiveness of the use of interactive learning tools at the stage of initial training in sports games - I.G. Maksimenko; G.N. Maksimenko; M.P. Spirin; V.V. Konovalov (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate rational schemes for the use of interactive teaching aids at the stage of initial training of athletes using the example of football. Methods and structure of the study. According to the idea of the study, at the 1st stage, the main aspects of the use of information technologies in the system of reserve training in sports games are summarized. At the 2nd stage, during a 10-month pedagogical experiment with the participation of two groups of athletes, 20 people each. (8-9-year-old boys, two years of training experience; at the beginning of the experiment, there were no significant differences in indicators) revealed patterns of using interactive teaching aids in weekly training cycles for athletes. Results and conclusions. Within the framework of the pedagogical experiment, the optimal schemes for the use of multimedia teaching aids in weekly training cycles of 8–9-year-old athletes are substantiated, which provide an increase in cognitive abilities, technical skills and psychophysiological qualities. It has been established that 8–9-year-old athletes are recommended to use interactive textbooks three times a week at the beginning of a lesson (duration up to 15 minutes); this scheme of using interactive programs in combination with traditional training means provides a statistical increase in indicators of technical skill, distribution of attention and cognitive abilities. Work with textbooks should be supervised and accompanied by a trainer; the volume of mastered material is determined by the requirements of the Federal standard for the sport.